Research networks and visualities: new settings for journalistic reflection - Borges, Rosane da Silva; Contani, Miguel (Brazilian journalism research, 2011)
This paper discusses the configurations of research networks in journalism. The focus is on the capillarity of the visual culture and the debates continuously reiterated regarding the epistemological code of communication. Why do newspapers keep investing massively in visual resources, operating structural changes in their make-up? In what name are these graphic-visual changes effected? The confluences between communication and visualities (in the plural in order to cover its immense variety and implications) are, as it seems, a non-deferrable confrontation involving contemporary changes in journalism. The formation of these networks thus relies on a variable and dynamic complexity, in an unlimited territory of exploration where simultaneities, ambiguities, levels of determination and indetermination play an important part. In conclusion, we argue that a theoretical-political principle must be encountered in order for the triad visualities, journalism and communication to be viewed in the ambit of research networks.